The effect of cover crops on soil quality indicators in a cereal and salad rotation. - Storr, Tom (Cranfield University, 2019)
Cover crop (CC)s influence soil function and thus affect crop yield and ecosystem services provided by soil. CCs are a relatively new soil management practice in U.K. agriculture, but are gaining in popularity amongst farmers. However, research on the effect of CCs on soil function in the short term and how to manage CCs effectively in the U.K. is limited. Therefore, field trials investigated the effect of CCs on physical (visual evaluation of soil structure, penetration resistance, bulk density, soil shear strength and soil moisture), chemical (total organic carbon and soil available nitrogen) and biological (earthworm abundance, microbial biomass and diversity) soil quality indicators, as well as crop yield. CCs were established between wheat and forage maize. A companion crop established with the maize remained overwinter after maize harvest until lettuce establishment the following spring. CCs placed between wheat and maize only affected available soil nitrogen with limited significant effects on other soil quality indicators. The addition of a companion crop significantly improved earthworm abundance, microbial community diversity and biomarkers associated with fungi. The companion crop significantly reduced bulk density and soil shear strength at 0.05 and 0.15m, respectively as well as penetrative resistance at 0-0.03m depth. Thus, continued plant presence, achieved through the establishment of cover and companion crops in the rotation allows for the accumulation of positive effects on soil quality and function in a short period of time (20months). Additionally, a survey distributed to U.K. farmers (n = 117) provided an understanding of the use, management and challenges associated with CCs. Respondents reported that the Basic Payment Scheme supporting CC use is not suitable and could be more flexible. Additionally, it took >3 years to realise benefits to soil structure. The knowledge gained from the survey can be used to inform future research and policy so that CCs can be implemented effectively to benefit the ecosystem services provided to the farmer and wider community.
PhD in Environment and Agrifood
Keywords: Field trial; survey